Impact of pharmacist-led intervention for reducing drug-related problems and improving quality of life among chronic kidney disease patients: A randomized controlled trial - Roheena Zafar; Inayat Ur Rehman; Yasar Shah; Long Chiau Ming; Khang Wen Goh; Amal K Suleiman; Tahir Mehmood Khan (PLoS ONE, 2025)
Introduction Chronic kidney disease (CKD) patients suffer from different comorbid conditions and are prone toward drug-related problems (DRPs) which affect their clinical parameters as well as quality of life (QoL). This study was aimed to evaluate the impact of clinical pharmacist-led interventions on the mean number of DRPs and the mean QoL score difference per patient DRPs in CKD patients. Method An open-labeled, randomized control trial performed from April 2023 to July 2023 in the nephrology unit of a tertiary care setting in Peshawar Pakistan. Those patients who met the inclusion criteria were randomized into two groups 1:1, i.e., control and intervention group. Clinical pharmacists identified the DRPs at baseline using Pharmaceutical Care Network Europe (PCNE) 9.1 guidelines. The QoL of patients were assessed at baseline and endpoint by using the Functional Assessment of Non-Life-Threatening Conditions (FANLTC) questionnaire. Results A total of 100 patients were recruited having 50 in each group. The pharmacist identified a total of n = 230 DRPs in the intervention group, majority of the DRPs were attributed to inappropriate drug selection according to guidelines/formulary”; “inappropriate combinations of drugs or with herbal medications or dietary supplements”; and situations where “too many different drugs or active ingredients were prescribed”. There was 46.52% reduction in the DRPs while comparing baseline and endpoint interventions suggested by pharmacist in the intervention group. The clinical pharmacist provided interventions in order to resolve the DRPs, and 37.40% interventions were accepted and fully implemented; 31.30% of the interventions were accepted and partially implemented. The clinical pharmacist identification and proposed intervention for DRPs contributed to a statistically significant improvement in QoL, from mean ±  SD scored 58.64 ±  9.10 at the baseline to 74.48 ± 10.11 at the endpoint, with a p-value of < 0.001. Conclusion A significant improvement in the QoL and laboratory parameters for patients with CKD following clinical pharmacist-led interventions having proposed interventions were implemented successfully from baseline to endpoint; however, a considerable number of proposed interventions were not accepted and implemented.